Edukasi pencegahan dan penanganan bullying disekolah Dasar Pandan wangi - Ria indah Kusuma Pitaloka (Karsa Bhakti : Journal of Community Service, 2025)
The phenomenon of bullying in elementary schools has become a serious issue that negatively affects students’ psychological, social, and academic development. This study aims to provide education on the prevention and management of bullying at Pandan Wangi Elementary School through a participatory and collaborative approach involving teachers, students, and parents. The research employed a descriptive qualitative method with activities such as counseling sessions, interactive discussions, role-playing simulations, and mentoring for school stakeholders. The educational activities focused on increasing students’ understanding of the types of bullying, its impacts, and preventive strategies through empathy, mutual respect, and positive communication. In addition, teachers received training on how to identify both victims and perpetrators of bullying and how to respond effectively based on character education principles and a restorative approach. The results showed an increased awareness among the entire school community about the importance of creating a safe, comfortable, and inclusive learning environment. Students became more confident in reporting incidents, teachers became more responsive in detecting negative behaviors, and parents were more open in communicating about their children’s behavior both at home and at school. This educational initiative is expected to serve as a sustainable model for building an anti-bullying culture at Pandan Wangi Elementary School and can be replicated in other elementary schools to create a child-friendly and violence-free educational ecosystem.